Harnessing bacterial antimicrobial peptides: a comprehensive review on properties, mechanisms, applications, and challenges in combating antimicrobial resistance - Erriah, Pirasannah; Puan, Sheau Ling; Mohd Yahaya, Normi; Wan Ahmad Kamil, Wan Nur Ismah; Amin Nordin, Syafinaz; Muhamad, Azira; Sabri, Suriana (Oxford University Press, 2024)
Antimicrobial resistance (AMR) is a significant global health concern due to the persistence of pathogens and the emergence of resistance in bacterial infections. Bacterial-derived antimicrobial peptides (BAMPs) have emerged as a promising strategy to combat these challenges. Known for their diversity and multifaceted nature, BAMPs are notable bioactive agents that exhibit potent antimicrobial activities against various pathogens. This review explores the intricate properties and underlying mechanisms of BAMPs, emphasizing their diverse applications in addressing AMR. Additionally, the review investigates the mechanisms, analyses the challenges in utilizing BAMPs effectively, and examines their potential applications and associated deployment challenges providing comprehensive insights into how BAMPs can be harnessed to combat AMR across different domains. The significance of this review lies in highlighting the potential of BAMPs as transformative agents in combating AMR, offering sustainable and eco-friendly solutions to this pressing global health challenge.